Battery Electrolytes: High‐Performance Lithium‐Oxygen Battery Electrolyte Derived from Optimum Combination of Solvent and Lithium Salt (Adv. Sci. 10/2017). Issue 10 (17th October 2017) - Ahn, Su Mi; Suk, Jungdon; Kim, Do Youb; Kang, Yongku; Kim, Hwan Kyu; Kim, Dong Wook
Abstract : The front cover image illustrates a redox shuttle reaction of NO2 − /NO2 molecules with a toroid‐shape lithium peroxide in the lithium oxygen battery for a possible application in electric vehicles. Oxygen gases are recovered from the lithium peroxide during the shuttle reaction, which is efficiently promoted in the solvent with high dielectric constant and good compatibility with lithium metal anode. Detailed mechanism and process are discussed in article number1700235 by Dong Wook Kim and his colleagues at Korea Research Institute of Chemical Technology.